Assessing the Role of E-Govqual in Improving Public Satisfaction with the MyPertamina Application in Setiabudi District: Mengkaji Peran E-Govqual dalam Meningkatkan Kepuasan Masyarakat terhadap Aplikasi MyPertamina di Kecamatan Setiabudi - Yulian Surya Saputra; Sucitra Sahara; Rizqi Agung Permana (NUANSA INFORMATIKA, 2025)
This research aims to analyze the influence of Customer Satisfaction on the quality of e-government services (E-Govqual) on the use of the My Pertamina application in Setiabudi District. The research method used was quantitative with a survey approach by distributing questionnaires to 150 respondents. The data collected was analyzed using validity tests, reliability tests, and hypothesis testing through linear regression analysis. The research results show that there is no significant influence between Customer Satisfaction and E-Govqual. This is proven by a correlation value of 0.160, which indicates a very weak relationship, as well as a coefficient of determination (R²) value of 2.56%, which indicates that variations in E-Govqual are only slightly influenced by Customer Satisfaction. The results of the hypothesis test show a significance value of 0.050 > 0.05 and Fcount (3.891) < Ftable (3.905), so that the null hypothesis (H₀) is accepted and the alternative hypothesis (H₁) is rejected. Satisfaction (X) on E-Govqual (Y) is 0.050 > 0.05, and the calculated F-value (F-count) is less than the F-table value, namely 3.891 < 3.905. These findings suggest that other factors beyond Customer Satisfaction may have a greater influence on e-government service quality. Based on the results, it is recommended that the development of the My Pertamina application be more focused on improving system quality, ease of use, and other technical aspects to improve overall service quality.